Urovirulence of Pseudomonas aeruginosa: planktonic cells vs. biofilm cells - Yadav, V; Harjai, K; Kaur, R; Joshi, K; Sharma, S (Folia microbiologica, 2004)
Planktonic and biofilm cells of a clinical urinary isolate of P. aeruginosa were compared in vitro for their ability to adhere to uroepithelial cells, interaction with macrophages, and for production of virulence factors like extracellular proteinase, elastase, hemolysin, phospholipase C and pyochelin. Biofilm cells showed increased adherence to UECs, which was coupled with reduced uptake and intracellular killing by macrophages. Overall there was a decrease in production of extracellular products by biofilm cells. Comparing the two cell forms for their ability to establish infection in an ascending model of acute pyelonephritis, significant enhancement of renal bacterial load, as well as more pronounced renal pathology developed with biofilm cells.
Keywords: Pyelonephritis; Virulence; Female; Mice; Pseudomonas aeruginosa; Mice, Inbred BALB C; zvířata; ženské pohlaví; plankton; virulence; biofilmy; pyelonefritida; Animals; Biofilms; myši inbrední BALB C; Plankton; myši